"The Argumentative Function of Intertextuality in the Political Discourse of Sheikh al-‘Arabi al-Tebessi" - lazhar, fares (El Omda in Linguistics and Discourse Analysis, 2018)
In the political discourse of Sheikh al-‘Arabi al-Tebessi (may God have mercy on him), we find seven types of argumentative intertextuality. The first is intertextuality with the Qur’an; the second, with Hadith; the third, with classical poetry; the fourth, with modern poetry; the fifth, with proverbs; the sixth, with popular heritage; and the seventh, with sermons. The diversity of argumentative intertextuality in the writings of Sheikh al-‘Arabi al-Tebessi—ranging across the Qur’an, Hadith, poetry (both classical and modern), proverbs, popular heritage, and sermons—stands as clear evidence of the breadth of his knowledge, the richness of his thought, his far-sightedness, and his ability to argue and persuade, as well as his mastery in constructing arguments. The effective use of these intertextual references is a strong indication of his literary talent, linguistic competence, and eloquence.